Essential variables for reporting research studies on fetal growth restriction: a Delphi consensus - Khalil, A; Gordijn, SJ; Beune, IM; Wynia, K; Ganzevoort, W; Figueras, F; Kingdom, J; Marlow, N; Papageorghiou, AT; Sebire, N; Zeitlin, J; Baschat, AA (Wiley, 2019)
Objective: To determine, by expert consensus using a Delphi procedure, a minimum reporting set of study variables for fetal growth restriction (FGR) research studies.